The race to improve care for athletes with atrial fibrillation - Elliott, A. D.; Lau, D. (Heart, Lung and Circulation, 2023)
The lifetime risk of atrial fibrillation (AF) is approximately 37% after the age of 55 years but increases with the accumulation of cardiovascular risk factors, including hypertension, obesity, and type 2 diabetes [ [1] ]. Lifestyle behaviours that reduce the development of these risk factors, including physical activity, are associated with lower risk of incident AF [ [2] ]. It is, therefore, of interest that participation in endurance sports is associated with increased risk of AF, despite lower overall prevalence of cardiovascular risk factors. Over the past three decades, the increased risk of AF among different populations of endurance athletes has been established among several groups, including former professional cyclists [ [3] ], long-distance cross-country skiing participants [ [4] ], and recreational athletes that include runners and triathletes [ [5] ]. It is important to recognise that, although these groups may include highly conditioned athletes performing competitively, this is not an issue necessarily confined to athletes of elite status (i.e., those performing at a national or international level in their respective sports). Recognition of AF management for athletes has been included in recent guideline documents although there remains an absence of randomised controlled trials to inform the treatment of AF specifically amongst athletes, and athletes are minimally represented among the participants of major clinical trials that inform these guidelines [ [6] , [7] ]. Therefore, current guidelines for this population are typically extracted from small, observational studies and expert consensus. The complexity of AF management in this population is often underappreciated, with objectives ranging from symptom management in the recreational sports participant to preservation of exercise performance for the elite performer, while also balancing risk factor management, rate control, rhythm control and oral anticoagulation therapy [ [8] ]. In this context, a recent article by Galloway et al. in Heart, Lung and Circulation provides interesting insights into the experiences and perspectives of male endurance athletes living with AF [ [9] ].